Influência de resíduos de rochas ornamentais nas propriedades de argamassas de revestimento - Melo, Rorennychollas Ferreira (Universidade do Vale do Rio dos Sinos, 2020)
The reuse of ornamental rock waste can provide benefits to cementitious matrices, providing a better destination for it. The following paper studies the partial replacement of cement by residual ornamental rocks (mud). The replacement took place in coating mortars, made with CP-V ARI cement, in the 1:1:6 line (cement, lime, sand). The water content was defined according to the consistency (fixed at 260 ± 5 mm). The potential for improving the properties of the mortar was evaluated from the determination of its granulometric distribution, the specific surface and the possibility of the waste to generate nucleation. The differences in the properties of the coating mortar were evaluated in the fresh and hardened state, and in the coating form. In the fresh state, the following properties were determined: consistency (spreading table), water retention and mass density. In the hardened state, the following properties were determined: compressive and tensile strength, mass density, volumetric variation, modulus of elasticity, water absorption by immersion, void index and water absorption by capillarity. In the coating, the tensile bond strength of the mortar applied in a ceramic block was evaluated. It is observed that the replacement of cement by waste of ornamental rocks influenced the mortars through the filer effect, acting on the physical effect, improving the granulometric packaging of the replaced mortars. The results indicate that the best content of substitution was 15% of cement for ornamental rock waste. The substitution did not compromise the performance of the produced mortar properties. Thereby, mortars with different contents of substitution obtained similar results to the reference mortar with lower levels of cement. The results obtained indicate that the ornamental rock waste has good potential to be used as filer in cementitious matrices.
Keywords: Resíduos; Rochas ornamentais; Argamassa de revestimento; Desempenho; Meio ambiente; Waste; Ornamental rocks; Coating mortar; Performance; Environment; ACCNPQ::Engenharias::Engenharia Civil